Identification by PCR signature-tagged mutagenesis of attenuated Salmonella Pullorum mutants and corresponding genes in a chicken embryo model. (March 2017) - Geng, Shizhong; Tian, Qin; Guo, Rongxian; Jiao, Yang; Barrow, Paul; Yin, Chao; Wang, Yaonan; Geng, Haopeng; Pan, Zhiming; Jiao, Xinan
Abstract: A key feature of the fowl-specific pathogen Salmonella Pullorum is its vertical transmission to progeny via the egg. In this study, PCR signature-tagged mutagenesis identified nine genes of a strain of S. Pullorum that contributed to survival in the chicken embryo during incubation. The genes were involved in invasion, cell division, metabolism and bacterial defence. The competition index in vivo and in vitro together with a virulence evaluation for chicken embryos of all nine mutant strains confirmed their attenuation. Highlights: Chicken embryo model infecting Salmonella pullorum were first made. Genes on vertical transmission of Salmonella pullorum were analyzed in a chicken embryo model by transposon mutagenesis. 9 genes were identified to cover invasion, cell division, metabolism and bacterial defence. 9 gene mutant strains were confirmed to be attenuated.